Patagonia : closing the loop on packaging pollution - Beckman, Sara Lynn; O'Neill, Kate, 1968-; Pendleton-Knoll, Seren; Rosenzweig, William; Strand, Robert, active 2019 (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2019)
Today, single-use packaging waste is invading all corners of the world, on land and in our oceans. Wholesale change is urgently needed to create packaging that does not wreak havoc on our planet. Due to complicated and global packaging supply chains, the quest for viable and sustainable improvements requires collaboration, innovative technologies, forward-thinking companies, consumer demand, and new government incentives and laws. This case demonstrates how Patagonia and other companies are actively seeking solutions to mitigate the single-use packaging crisis and, by 2025, use biodegradable, recyclable, or reusable packaging, and the challenges associated with doing so.
Originally Published InBeckman, S., O'Neill, K., Pendleton-Knoll, S., Rosenzweig, W., & Strand, R. (2019). Patagonia: Closing the Loop on Packaging Pollution. The Berkeley-Haas Case Series. University of California, Berkeley: Haas School of Business.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Patagonia, Inc. -- Case studies; Packaging waste -- Environmental aspects -- Case studies; Packaging waste -- Recycling -- Case studies